وسائل الإثبات المعاصرة في الفقه الجنائي الإسلامي - مناني, بشيرة; مناني, صفاء; خلف, منجية (University of Eloued-جامعة الوادي, 2018)
درس هذا البحث موضوع أدلة الإثبات في الفقه الجنائي الإسلامي، وقُسم إلى أربعة أقسام، أما الجزء الأول فقد كان تمهيديا عُرفت فيه وسائل الإثبات وكذلك الفقه الجنائي، والثاني تطرق للإقرار وبيان حجيته وأحكامه، بينما درس الثالث الشهادة واليمين وبين حجيتهما وأحكامهما، وجاء في القسم الأخير بيان البينة ثم تم التطرق لبعض الوسائل المعاصرة في الإثبات الجنائي؛ بصمة اليد والبصمة الجينية وتحليل الدم. The abstract This study examined the subject of evidence evidence in the Islamic Criminal Jurisprudence, divided into four sections The first part was a preliminary in which the means of proof as well as the criminal jurisprudence were known, and the second was related to acknowledgment the statement of its validity and judgments , while the third examined the testimony and the right between their arguments and judgements Evidence was then given to som. contemporary methods of forensic evidence; fingerprints, genetic fingerprinting and blood analysi.
مذكرة ليسانس
Keywords: الإثبات /الفقه الجنائي الإسلامي; Preuve/jurisprudence pénale islamique